PENGARUH LEVERAGE, LIKUIDITAS, DAN AKTIVITAS TERHADAP PERTUMBUHAN PROFITABILITAS (Studi Pada Perusahaan LQ-45 yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2013-2015) - Hani Majdina Adha; Sri Sulasmiyati (Jurnal Administrasi Bisnis, 2017)
This research aims to analyis and examine; 1) Influence of Debt to Assets Ratio (DAR) on Profit Growth; 2)Influence of Debt to Equity Ratio (DER) on Profit Growth; 3) Influence of Current Ratio (CR) on Profit Growth; and 4) Influence of Total Assets Turnover (TATO) on Profit Growth. The kind of research used in this research is an explanation or explanotory research with a quantitative approach. The variable in this research is Debt to Assets Ratio (DAR), Debt to Equity Ratio (DER), Current Ratio (CR), and Total Assets Turnover (TATO) as independent variables and the Profit Growth as the dependent variable.The result of this research indicate that: 1) Leverage, Liquidity, and Activity simultaneously significant effect on Profitability Growth; 2) T test result indicate that the Debt to Assets Ratio (DAR) and Debt to Equity Ratio (DER) significantly influence the Profit Growth. Instead, Current Ratio (CR) and Total Assets Turnover (TATO) insignificantly influence the Profit Growth. Keywords: Debt to Assets Ratio (DAR), Debt to Equity Ratio (DER), Current Ratio (CR), Total Turnover Assets (TATO), and Profit Growth. ABSTRAK Penelitian ini bertujuan untuk menganalisis dan menguji: 1) Pengaruh Debt to Assets Ratio (DAR) terhadap Pertumbuhan Laba; 2) Pengaruh Debt to Equity Ratio (DER) terhadap Pertumbuhan Laba; 3) Pengaruh Current Ratio (CR)terhadap Pertumbuhan Laba; dan 4) Pengaruh Total Assets Turnover (TATO) terhadap Pertumbuhan Laba. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian penjelasan atau explanatory research dengan pendekatan kuantitatif. Variabel dalam penelitian ini adalah Debt to Assets Ratio (DAR), Debt to Equity Ratio (DER), Current Ratio (CR) , dan Total Assets Turnover (TATO) sebagai variabel bebas dan Pertumbuhan Labasebagai variabel terikat. Hasil peneitian ini menunjukkan bahwa: 1) Leverage, Likuiditas, dan Aktivitas secara simultan berpengaruh signifikan terhadap Pertumbuhan Profitabilitas; 2) Hasil uji t menunjukkan bahwa variabel Debt to Assets Ratio (DAR) dan Debt to Equity Ratio (DER) berpengaruh signifikan terhadap Pertumbuhan Laba. Sebaliknya, variabel Current Ratio (CR) dan Total Asssets Turnover (TATO) tidak berpengaruh signifikan terhadap Pertumbuhan Laba. Kata Kunci:Debt to Assets Ratio (DAR), Debt to Equity Ratio (DER), Current Ratio (CR), Total Assets Turnover (TATO), dan Pertumbuhan Laba.